(untitled) (Bangladesh Journal of Microbiology, 2019)
Foods may become contaminated from a variety of sources, therefore it is imperative to understand and discover easy, cheap and effective means of decontaminating foods. Heat, although effective, economical and easily available, has been reported to produce undesirable effects on food such as loss of taste and nutrition. High Pressure Processing can inactivate the cells of the food borne pathogens and organisms responsible for food spoilage regardless of the temperature without making changes to the texture, color or flavor. Equipment involved in HPP includes a pressure vessel, pumps generating high hydrostatic pressure or intensifiers. Its success depends on certain factors such as pressure of water, temperature used during the treatment, and the properties and state of the food and categories of microorganisms found in food.Cold Plasma Technology (CPT) is a novel, non-thermal food processing technology that uses energetic and reactive gases to inactivate contaminating microorganisms in food products. CPT is environmentally friendly that uses natural gases such as nitrogen, argon, air, hydrogen, and oxygen. Depending on the plasma type, it can inactivate a wide range of microorganisms including food borne pathogens and spoilage organisms. This technology hasa low running cost (Cost of natural gases and electricity).Both HPP and CPT can spread and work on the entire food sample, regardless of shape and size. These methods serve as an alternative to some methods which were previously used. Bangladesh J Microbiol, Volume 36 Number 1 June 2019, pp 35-43